Immune-related adverse events associated with nab-paclitaxel/paclitaxel combined with immune checkpoint inhibitors: a systematic review and network meta-analysis - Hao, Wenjing; Zhang, Jun; Wang, Yunxia; Fang, Boyu; Jin, Shasha; Yuan, Jing; Cai, Weimin (Frontiers in Immunology, 2023)
Objective: The combination of nanoparticle albumin-bound paclitaxel (nab-PTX)/paclitaxel (PTX) with immune checkpoint inhibitors (ICIs) has demonstrated significant efficacy in cancer patients. However, the safety of these combination regimens remains conflicting in former researches. Therefore, in order to address this issue, we performed a systematic review and network meta-analysis (NMA) to evaluate and compare the safety profile. Methods: We performed a systematic review by searching randomized controlled trials (RCTs) from PubMed, EMBASE, Cochrane Library, ClinicalTrials.gov, and Web of Science up to August 15, 2022. The primary outcomes were all‐grade (grade 1‐5) and high‐grade (grade 3‐5) immune-related adverse events (irAEs). Secondary outcomes were all‐grade (grade 1‐5) and high‐grade (grade 3‐5) irAEs of subgroups of ICIs. Results: There were 22 RCTs included in the NMA, involving a total of 15 963 patients diagnosed with any type of cancer. ICIs+nab-PTX was associated with a noticeably decreased risk of grade 3-5 pneumonitis (odds ratio [OR]=0.28, 95% credible interval [CrI]: 0.09,0.90) compared to ICI monotherapy; ICIs+PTX showed a lower risk of grade 1-5 hyperthyroidism (OR=0.46, 95% CrI: 0.22-0.96) and grade 1-5 hypothyroidism (OR=0.49, 95% CrI: 0.26-0.93) than ICIs. Compared with PD-1, PD-1+PTX was associated with a statistically significantly lower risk of grade 1-5 pneumonitis (OR=0.32, 95% CrI: 0.11-0.92). PD-L1 resulted in a noticeably lower risk of grade 1-5 hypothyroidism (OR=0.34, 95% CrI: 0.12-1.00) than PD-L1+PTX. Nearly all treatment regimens containing ICIs demonstrated significantly higher risks of irAEs compared to the standard chemotherapy groups. Conclusion: Nab-PTX/PTX+ICIs demonstrated an approach leading to decreased risk of irAEs compared with ICI monotherapy. This finding supports that ICIs+nab-PTX/PTX may be a safer treatment strategy. Moreover, we also found that the combination regimens containing ICIs had a higher risk of irAEs than standard chemotherapy. Additionally, ICIs+nab-PTX demonstrated a decreased risk of irAEs compared to ICIs+PTX. PD-1 inhibitors were associated with a higher risk of irAEs than PD-L1 inhibitors.